Generation of Useful Hydrocarbons and Hydrogen during Photocatalytic Decomposition of Acetic Acid on CuO/Rutile Photocatalysts - Sylwia Mozia (International Journal of Photoenergy)
The presented studies have focused on a photocatalytic generation of useful hydrocarbons, mainly methane and ethane, from acetic acid under N2 atmosphere. CuO-loaded rutile, as well as unmodified rutile and anatase-phase TiO2 photocatalysts were applied in the experiments. The efficiency of the catalysts towards methane generation changed in the following order: Cu-TiO2 (10% Cu) > crude TiO2≈Cu-TiO2 (20% Cu) > Cu-TiO2 (5% Cu) > rutile. The amount of CH4 produced in the presence of the catalyst containing 10 wt% of Cu was higher for ca. 33% than in case of pure rutile. The concentration of ethane was 14–16 times lower than the amount of methane, regardless of the catalyst used. Low concentrations of hydrogen were also detected in the gaseous mixtures. After 5 hours of the process conducted with the catalyst containing 5–20 wt% of Cu the concentration of hydrogen amounted to 0.06–0.14 vol.%, respectively.